Modern Education Forms And Methods - Rajabov Khusinboy Zokirjon Ogli (Zien Journals, 2024)
This article focuses on modern forms and methods of education. The article analyzes the history of "blended learning", organization of training, technologies of the educational system. The importance of modern educational forms and methods in the educational process is revealed.
Keywords: Modern lesson; blended learning; information technologies